PENGARUH LITERASI KEUANGAN, EFIKASI KEUANGAN, PERILAKU KEUANGAN, DAN FAKTOR DEMOGRAFI TERHADAP PENGAMBILAN KEPUTUSAN MENABUNG: (Studi Kasus Pada Mahasiswa Manajemen Universitas PGRI Semarang) - Febriliantino, Edofahnni; Indriasari, Ika; Darmaputra, M Fadjar (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2024)
The purpose of this study is to investigate and assess the impact of financial literacy, financial efficacy, financial behavior, and demographic characteristics on saving decisions (using a case study of management students at PGRI University Semarang). The descriptive research method was used in this study. The research population consisted of all UPGRIS students from the Faculty of Economics and Business, Class 2019-2021. The sample in this study was 100 respondents, and the sampling strategy utilized in the research was purposive sampling, which meant that subjects were chosen not based on stratification, randomness, or regionality, but on the existence of a specific purpose. This study's data gathering method was a questionnaire distributed to 100 management students at PGRI University Semarang between 2019 and 2021. According to the study's findings, financial literacy and demographic characteristics have a large positive effect on the decision to save, whereas financial efficacy and financial conduct have a significant negative effect. Keywords: financial literacy, financial efficacy, financial behavior, demographic factors and saving decisions